Influence on Aerobic Fitness on Aortic Stiffness in Apparently Healthy Caucasian and African-American Subjects - Arena, Ross (2007)
BACKGROUND: Previous research suggests that arterial stiffness may be significantly higher in African-Americans compared to Caucasians. However, the influence of aerobic fitness on the putative difference in arterial stiffness between these groups has not been previously investigated. METHODS: Two hundred forty-eight subjects (215 Caucasian, 33 African-American) participated in this study. Within one week following enrollment, subjects underwent body mass index (BMI, kg/m(2)) assessment, cardiopulmonary exercise testing and measurement of aortic wave velocity (AWV, m/s) via magnetic resonance imaging. Initially, 33 Caucasian subjects were randomly age (±4 years) and sex-matched (10 male/23 female) to the African-American subjects. 25 Caucasian subjects were then randomly matched for age (±4 years), sex (7 male/18 female) and maximal oxygen consumption (VO(2Max)±7 mlO(2)●kg(−1)●min(−1)) to the African-American subjects. Matching based upon VO(2Max) criteria was not possible for 8 African-American subjects. RESULTS: In the age and sex-matched analysis, Caucasian subjects demonstrated a significantly higher VO(2Max) (38.3 ±9.6 vs. 27.9 ±8.6 mlO(2)●kg(−1)●min(−1), p<0.001) and lower BMI (24.5 ± 3.2 vs. 29.3 ±6.2 kg/m(2), p<0.001) and AWV (5.8 ±1.7 vs. 6.7 ±1.5 m/s, p=0.03). However, when subjects were matched for age, sex and VO(2Max), the differences in both BMI (26.8 ±5.5 vs. 27.9 ±5.6 kg/m(2), p=0.45) and AWV (6.1 ±1.8 vs. 6.5 ±1.6 meters/second, p=0.77) were insignificant. CONCLUSIONS: The results of the present study suggest that previously reported differences in arterial stiffness between Caucasians and African-Americans is at least partially a consequence of a lower level of aerobic fitness in the latter group, a phenomenon that has also been previously demonstrated.